Does the Owl Fly Out of the Tree or Does the Owl Exit the Tree Flying? How L2 Learners Overcome Their L1 Lexicalization Biases. Issue 1 (2nd January 2016) - Song, Lulu; Pulverman, Rachel; Pepe, Christina; Golinkoff, Roberta Michnick; Hirsh-Pasek, Kathy
ABSTRACT: Learning a language is more than learning its vocabulary and grammar. For example, compared with English, Spanish uses many more path verbs such as ascender ('to move upward') and salir ('to go out'), and expresses manner of motion optionally. English, in contrast, has many manner verbs (e.g., run, jog ) and expresses path in prepositional phrases (e.g., out of the barn). The way in which a language encodes an event is known as its lexicalization pattern or bias . Using a written sentence elicitation task, we asked whether adult Spanish learners whose L1 was English adopted Spanish lexicalization biases, and what types of L2 exposure facilitated the learning of lexicalization biases. Results showed that advanced, but not intermediate, adult Spanish learners showed a path bias comparable to that found in native speakers of Spanish. Furthermore, study abroad experience is associated with better acquisition of L2 lexicalization biases when describing certain types of events.